The Effect of Compensation and Job Satisfaction on Turnover Intention in Employees of PT. DOK and Perkapalan Surabaya (Persero) - Muhammad Hafis Fauzi (Lavish Opulent Education, 2024)
Human resources are an important aspect in a company in order to exist in the era of global competition. The purpose of this research is to Influence Compensation and Job Satisfaction Against Turnover Intention Employees at PT Dok and Perkapalan Surabaya (Persero). The population in this study were all employees at the PT Dok and Perkapalan Surabaya (Persero) as many as 69 respondents. The research method used in this research is quantitative method. The data analysis method used is regression analysis using the SPSS 24.0 application. Based on the research that has been done at the PT Dok and Perkapalan Surabaya (Persero), the following conclusions are obtained: Compensation has a significant effect on turnover intention employees at PT Dok and Perkapalan Surabaya with t count (1,805) and a significant value of 0.008 <0.05; Job satisfaction has a significant effect on turnover intention employees at the PT Dok and Perkapalan Surabaya with a t count (0,221) with a significant value of 0,026 <0,05. The results of data analysis reveal that compensation and job satisfaction have significant effect on PT Dok and Perkapalan Surabaya (Persero) employee turnover intention as directly. Based on the results of the study above, compensation and job satisfaction provide a very significant contribution to the turnover intention of employees of PT Dok and Perkapalan Surabaya (Persero). Therefore, efforts need to be made to increase compensation and job satisfaction in order to reduce the number of turnover intention.